2014
DOI: 10.3389/fnhum.2014.00968
|View full text |Cite
|
Sign up to set email alerts
|

Viewing photos and reading nouns of natural graspable objects similarly modulate motor responses

Abstract: It is well known that the observation of graspable objects recruits the same motor representations involved in their actual manipulation. Recent evidence suggests that the presentation of nouns referring to graspable objects may exert similar effects. So far, however, it is not clear to what extent the modulation of the motor system during object observation overlaps with that related to noun processing. To address this issue, 2 behavioral experiments were carried out using a go-no go paradigm. Healthy partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 75 publications
8
44
5
1
Order By: Relevance
“…We assessed the compatibility effects for objects and words and found results consistent with previous findings in that both objects and words significantly modulated motor responses517. These results support the embodied cognition accounts which hold that access to motor codes is an integral part of object perception23.…”
Section: Discussionsupporting
confidence: 86%
“…We assessed the compatibility effects for objects and words and found results consistent with previous findings in that both objects and words significantly modulated motor responses517. These results support the embodied cognition accounts which hold that access to motor codes is an integral part of object perception23.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, a specific modulation of hand motor responses has been shown during the processing of nouns referring to hand-related objects (Marino et al, 2013 ), as compared to foot-related objects. Two recent studies (Marino et al, 2014 ; Zhang et al, 2016 ) showed a similar modulation of the motor system during the processing of objects and nouns belonging to the same category. Additionally in an fMRI study (Desai et al, 2016 ), during reading nouns expressing graspable objects activations were found in areas also involved in action performance, thus supporting a grounded view of semantics.…”
Section: Introductionmentioning
confidence: 75%
“…For instance, in a simple task involving reaching for blocks and picking them up, grasping kinematics are influenced by text printed on the blocks, such as 'long' or 'short', as well as by words representing relative large or small objects (e.g., ' apple' or 'grape') (Gentilucci et al, 2000;Gentilucci & Gangitano, 1998;Glover et al, 2004). In the opposite direction, motor congruency of objects and pictures of objects, such as the side of a handle can influence response time and other measures in cognitive tasks (Brouillet et al, 2015;Buccino et al, 2009;Chum et al, 2007;Handy et al, 2003;Marino et al, 2014;Oakes & Onyper, 2017;Tucker & Ellis, 1998). Even more broadly, words and pictures representing objects varying in functionality can influence attention, semantic processing, and memory (Hauk et al, 2004;Madan et al, 2016;Madan & Singhal, 2012a;Montefinese et al, 2013;Pulvermüller, 2005;Shebani & Pulvermüller, 2013;Tousignant & Pexman, 2012;Witt et al, 2010).…”
Section: Other Motivational Factorsmentioning
confidence: 99%